Current state of the problem of human papillomavirus infection - L. A. Yusupovа; E. I. Yunusovа; Z. Sh. Garaeva; G. I. Mavlyutova; K. A. Salakhutdinova (Лечащий Врач, 2021)
The article presents data on papillomavirus infection caused by human papilloma virus (HPV). The etiological and pathogenic mechanisms leading to the development of the disease are given, the risk factors for HPV infection, the clinical picture of different forms of the disease are described in detail. The article reveals information about the diagnosis of papillomavirus infection and tactics of treatment of patients with HPV infection.